2010
DOI: 10.1159/000313586
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Physical Training Decreases mRNA Levels of Glucocorticoid Receptor and Inflammatory Genes

Abstract: Background/Aims: Prolonged physical exercise induces adaptive alterations in the hypothalamic-pituitary axis, increasing cortisol metabolism, and reducing cortisol synthesis and glucocorticoid sensitivity. The mechanisms responsible for this relative glucocorticoid resistance remain unknown but may involve expression of genes encoding glucocorticoid receptor (GR) and/or inflammatory molecules of nuclear factor kappa B1 (NFkB1) signaling pathway and cytokines. This study aimed to determine the impact of prolong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 60 publications
2
8
0
2
Order By: Relevance
“…28 Lambert et al 3 found that mRNAs for proteins involved in inflammation were significantly reduced by 12 weeks of aerobic and resistance-training exercise but not by weight loss in obese elderly individuals with functional impairment. 3 Sousa et al 35 found that prolonged physical exercise reduced mRNA levels of NF-κB1, inhibitor of Nf-κB1, and Ikβ kinase A. Researchers also observed a concomitant reduction in cytokine concentrations.…”
Section: Repeated Boutsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Lambert et al 3 found that mRNAs for proteins involved in inflammation were significantly reduced by 12 weeks of aerobic and resistance-training exercise but not by weight loss in obese elderly individuals with functional impairment. 3 Sousa et al 35 found that prolonged physical exercise reduced mRNA levels of NF-κB1, inhibitor of Nf-κB1, and Ikβ kinase A. Researchers also observed a concomitant reduction in cytokine concentrations.…”
Section: Repeated Boutsmentioning
confidence: 99%
“…[19][20][21] Other research has investigated the relationship between cytokines and muscle damage more directly by comparing cytokine responses to concentric versus eccentric actions, 19,[22][23][24][25] submaximal versus maximal eccentric contraction, [26][27][28][29][30][31] and single versus repeated bouts of eccentric exercise. 23,28,[32][33][34][35] …”
Section: Exercise and Inflammationmentioning
confidence: 99%
“…In 18 male cadets in the Brazilian Air Force Academy, 6 weeks of intensive exercise training led to a reduction in basal cortisol levels, and in glucocorticoid receptor (GR) mRNA levels and decreased glucocorticoid sensitivity, measured as the response to intravenous low‐dose dexamethasone 45, 46. Binding capacity of GRs in peripheral blood monocytes was lower in semiprofessional soccer players than in young and older comparison subjects 47. Highly trained swimmers had substantially lower GR‐α mRNA expression than untrained control subjects 48.…”
Section: Discussionmentioning
confidence: 99%
“…Few other studies in the literature have examined NFkB and exercise, however, in a similar experimental paradigm, neither cafeteria diet nor exercise were found to affect NFkB mRNA in hippocampus or PFC of mice (Auer et al, 2015), although the diet used in that study was significantly different from the Western diet used in the present study, which may partially explain the discrepant results. In humans, it has been shown that prolonged physical training also decreased mRNA expression of multiple NFKB-related genes in blood (Sousa e Silva et al, 2010). When considered on a single gene level, voluntary exercise (as opposed to forced) appeared to exert little effect on the proinflammatory profile in the prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%